Characterizing impulsivity in individuals with methamphetamine and methcathinone use disorders - Yin, Jie; Cheng, Xinyu; Zhou, Chendi; Xu, Lin; Yang, Bo; Yuan, Ti-Fei (Frontiers in Psychiatry, 2024)
Background: Individuals with substance use disorder (SUD) are characterized by loss of control in drug use, such as increased impulsivity. Methamphetamine and methcathinone are psychostimulants, the use of which is accompanied by a high level of impulsivity. Whether individuals with methamphetamine use disorder (MUD) and methcathinone use disorder (MCUD) differ in different aspects of impulsivity is unclear.We investigated impulsivity traits and behaviors in individuals with MUD and MCUD.The Barratt Impulsiveness Scale (BIS), Sensation Seeking Scale (SSS) and delay discounting task (DDT) were assessed in individuals with MUD, MCUD, and in healthy controls (HCs); then, we performed network-based analysis and computational modeling to understand the potential differences among the three groups.Results: MUD subjects scored higher than MCUD subjects in terms of motor impulsivity, nonplanning impulsivity and total BIS scores. Network analysis revealed that there were no significant differences between MUD and MCUD subjects in any centrality indices. The discount rate of MUD and MCUD subjects was significantly greater than that of HCs, whereas there was no difference in the discount rate between the two addiction groups.Conclusions: These findings suggest that MUD and MCUD participants differ in impulsivity traits but not in impulsive behaviors, implying that impulsive traits and behaviors represent different aspects of impulsivity.